Theater as a Media to Introduce Papuan Culture to Millennial Generation - Cedric Louise Tanamas; Natasia Surya Santosa; Natasya Cristiani (Universitas Muhammadiyah Sidoarjo, 2020)
Papua is often considered and viewed as a primitive tribe and second class people, but on the other hand Papua has a diverse and beautiful culture that can be used as a national cultural heritage. In the era of globalization, many new values ​​enter and create a new world unity value, globalization also causes the flow of information to be very fast and easy to access, this also brings foreign cultures to Indonesia very easily. Millennials are more interested in foreign cultures which can cause local cultures to become extinct over time. In anticipating this,strategiesare needed to continue to maintain and preserve cultures, by introducing local culture, especially Papuan culture to the millennial generation in an educative and entertaining way. Performing arts can be an effective communication medium in delivering messages because they involve the audience and provide real experience. Theater is one of the performing arts that involves audio and visual. Millennial generation's interest in theater performances is high. Thus theater performances can be an effecctive communication medium to introduce Papuan culture to the millennial generation.